Development of Self Esteem-Oriented Micro Teaching Materials for IAIN Palopo English Education Students - Husnaini Husnaini (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this research is to produce teaching materials for Micro teaching subject based on Self Esteem to students of the English Education Study Program with dimensions of respect and self-respect, courage and ability in communication and confidence in one's own abilities. The elements in the module are tips and motivation, exercises/practices and summaries and formative tests in each chapter. The module was developed by taking into account the value of its validity, practicality and effectiveness. The approach used in the research is Research and Development research or development with the ADDIE development model. The trial was conducted on 5th semester students in the English Education study program, Palopo State Islamic Institute. The output in this research is a module for microteaching teaching and is published as an ISBN book by IKAPI member publishers.